PEPTIC ULCER DISEASE: CHANGE OF NOTIONS AND APPROACHES, ACCENTS TO THE HEART RATE VARIABILITY - Tоmina, Е.Е.; Yabluchanskіy, N.I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Peptic ulcer etiology, pathogenesis and therapy literature review is offered. With the reoccurrence of interest to the meaning of autonomous nervous system in the genesis of ulceration, the research of regulatory processes using heart rate variability (HRV) analysis becomes strongly actual. Latest publication that contain separate HRV investigations in peptic ulcer patients are given.